Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1016/j.dib.2019.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Dataset on optimization of EDM machining parameters by using central composite design

Abstract: Newly prepared titanium alloy (Ti-13Zr-13Nb (TZN)) using powder metallurgy is considered in this investigation. Titanium alloys (TZN) are used in hip and knee replacement for orthopedic implants. Conventional machining, TZN alloys produce higher tool wear rate and poor surface quality, but this can be reduced by Electrical Discharge Machining (EDM) method. Moreover, EDM produce good biological and corrosion resistant surface. In this research, experiments were conducted by considering the influential process f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 10 publications
5
18
0
Order By: Relevance
“…An experimental dataset on EDM machining parameters by using the central composite design reported by Soundhar et al [31] is considered in this case study. Titanium alloy (Ti-13Zr-13Nb), i.e., TZN, was used as the work material for EDM machining.…”
Section: Experimental Backgroundmentioning
confidence: 99%
See 3 more Smart Citations
“…An experimental dataset on EDM machining parameters by using the central composite design reported by Soundhar et al [31] is considered in this case study. Titanium alloy (Ti-13Zr-13Nb), i.e., TZN, was used as the work material for EDM machining.…”
Section: Experimental Backgroundmentioning
confidence: 99%
“…Production of TZN can be done using different processes like the blended elemental method, cold uniaxial pressing, cold isostatic pressing and vacuum sintering. Soundhar et al [31] used a hydrated-dehydrated process for making titanium powder. The detailed method followed by Soundhar et al [31] is as follows-titanium powder was produced using a vertical furnace at a temperature of 500 • C and timing of 3 h with positive pressure.…”
Section: Experimental Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…Under such circumstances, the effective utilization of experimental, modeling, and optimization methodology make possible a more considerable improvement in decision-making with a new technological solution that can simultaneously satisfy and control the several distinctive as well as contradictory objectives (multi-objective) in order to make the EDM process an excellent choice for machining of advanced metal matrix composite materials. Several statistical and computational approaches such as RSM [16][17][18][19][20][21], ANN [22][23][24][25][26][27] have been applied for predictive modeling and Taguchi method [28][29][30][31], GRA [32][33][34][35][36], desirability function approach of RSM [37][38][39][40], and PCA [41,42] have been employed for parametric as well as process optimization in electrical discharge machining. Extensive studies have been reported by employing various experimental designs, modeling techniques and optimization approaches in order to assess or investigate the machinability [43][44][45][46], to predict the various technological responses, and to control the process parameters in machining of different workpiece materials (AISI D2, D3, D6, MDN 300, AISI 316L, stainless steel, A 2 tool steel, grey cast iron, Inconel 600, 601, 625, 825, 718, Ti6Al4V, Ti13Zr13Nb, nickel alloy, Al7075, Al6061, Al6063 alloy, Al-SiC MMC, Si 3 N 4 -TiN MMC, Al-Mg 2 Si, WC, polycrystalline diamond).…”
Section: Introductionmentioning
confidence: 99%